2021
DOI: 10.3390/nano11113049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyrtostachys renda Fiber Loading on the Mechanical, Morphology, and Flammability Properties of Multi-Walled Carbon Nanotubes/Phenolic Bio-Composites

Abstract: This research focuses on evaluating the effect of Cyrtostachys renda (CR) fiber and the impact of adding multi-walled carbon nanotubes (MWCNT) on the morphological, physical, mechanical, and flammability properties of phenolic composites. MWCNT were supplemented with phenolic resin through a dry dispersion ball milling method. Composites were fabricated by incorporating CR fiber in 0.5 wt.% MWCNT-phenolic matrix by hot pressing. Nevertheless, the void content, higher water absorption, and thickness swelling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…It has been shown that nanoparticles [31,32], polymers [33][34][35][36], and nanocomposites [37] could be used for water treatment. TOPSIS has been used for the selection of polymers [38][39][40][41], nanomaterials [42][43][44], and machine process parameters [45]. It has been shown to be efficient for optimizing analytic procedures and normalization methods [46,47], and materials [48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that nanoparticles [31,32], polymers [33][34][35][36], and nanocomposites [37] could be used for water treatment. TOPSIS has been used for the selection of polymers [38][39][40][41], nanomaterials [42][43][44], and machine process parameters [45]. It has been shown to be efficient for optimizing analytic procedures and normalization methods [46,47], and materials [48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…During recent years, TOPSIS has been used for the optimization and analysis of polymers [50][51][52][53], nanomaterials [54][55][56], and machine process or operation parameters [57][58][59][60]. More investigations would be required to develop this algorithm for the manufacturing optimization of materials and their preparation procedures for environmental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally it is found that a group led by Loganathan also reported in their multiple studies about possible improvements in mechanical, tribological, and thermal properties for a hybrid of fiber reinforcements and carbon nano fillers in phenolic resin nanocomposites using mechanical ball milling (dry dispersion) has been reported. 138,178,179 Moreover, there were numerous works that used different methods to process the dispersion of unmodified or modified nanocarbon reinforcements/fillers in phenolic matrix nanocomposite such as CVD, ball milling, sonication, or hybridizations thereof. [180][181][182][183][184][185][186]…”
Section: Nanocarbon Modifier (Wt%)mentioning
confidence: 99%